Effects of bilateral arm training on upper extremity function in right and left hemispheric stroke - Humera Ambreen; Hina Tariq; Imran Amjad (Journal of the Pakistan Medical Association, 2020)
Objective: This experimental study on 24 stroke patients aimed at evaluating and comparing the effects of bilateral arm training on upper extremity (UE) motor function between right and left hemispheric chronic stroke patients. Methods: Both groups received the same intervention involving 5 functional tasks for 1 hour, 3 days per week, for a total of 6 weeks. Fugl-Meyer Assessment-Upper Extremity and Wolf-Motor Function Test were applied as outcome measures at baseline and after 6 weeks of training to assess the recovery of function in the affected area. Results: Intra-group analysis showed no significant improvement in the wrist and hand function in the left hemispheric stroke (LHS) (p>0.05), while right hemispheric stroke (RHS) patients did not improve significantly in the coordination/speed domain (p>0.05). Inter-group analysis showed no significant difference between right and left hemispheric stroke patients (p>0.05). Conclusion: Bilateral arm training showed beneficial effects in improving UE function in both RHS and LHS patients. Distal UE function in LHS and coordination and speed of movement in RHS patients did not show any significant improvement. Key Words: Stroke, Upper extremity, Recovery of function, Bilateral arm training. Continuous...